2010
DOI: 10.1007/s00199-010-0517-2
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between hierarchy and type morphisms

Abstract: Here, we establish a relationship between hierarchy and type morphisms. Both concepts have been used to relate the types in one structure to types in a second "larger" structure. In general, the two concepts may di¤er, in the sense that a hierarchy morphism need not be a type morphism. We provide a necessary and su¢ cient condition under which the two concepts coincide. We go on to provide situations under which this condition must be satis…ed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…A number of papers has shown that the measurable structure associated with type structures can impose restrictions on reasoning [12,[20][21][22][23]. This paper contributes to that literature in two ways.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…A number of papers has shown that the measurable structure associated with type structures can impose restrictions on reasoning [12,[20][21][22][23]. This paper contributes to that literature in two ways.…”
Section: Introductionmentioning
confidence: 87%
“…The second test uses type morphisms. Type morphisms are defined solely in terms 1 We follow the terminology of Friedenberg and Meier [12] here. A stronger condition for T to be contained in T is that T can be embedded (using a type morphism) into T as a belief-closed subset [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations